A quality control circle process to improve enteral nutrition feeding support in discharged patients with colorectal cancer - Lin, Youyan; Yu, Xinyan; Ni, Xiaoyu; Shu, Wenxi; Zheng, Qiuhong; Chen, Fengzhou; Zhang, Bo; Xu, Chao; Liu, Ling; Lu, Yi (Frontiers in Nutrition, 2023)
Correct usage and maintenance of the enteral nutrition feeding pump system is always a challenge in nutrition support for patients with colorectal cancer (CRC). However, there are few studies on the sustained accuracy improvement of the enteral nutrition feeding system in discharged CRC patients. Here, we established a seven-month quality control circle (QCC) activity with the theme of improving the performance of home enteral feeding pumps (EFP) and examined the effect of QCC activity on the nutritional state and quality of life in discharged CRC patients. We enrolled 100 discharged CRC patients treated with home enteral nutrition from Zhejiang Cancer Hospital between Mar. 2020 and Dec. 2021. The patients were randomly split into two research groups: one participated in the QCC activity (n=50) and the other did not (n=50). QCC analysis indicated that the top 3 causes of EFP inaccurate usage are the simple and boring contents of training, various types of pumps, no examination rules, and lack of management. Furthermore, both intra-and inter-group comparisons showed that QCC significantly improved the patients' pass rate of nutrition pump operation from 52% to 70% after 1-month of activity, which gradually improved and got the highest (90%) after 3 months (P<0.05). Interestingly, the established QCC activity significantly increased the patient-generated subjective global assessment (PG-SGA) and Barthel index (BI) scores, body fat mass (BFM) and superior longitudinal muscle (SLM) by intra-and inter-group comparisons. In this study, we clarified the main causes of inaccurate EFP usage and established a QCC process to improve the pass rate of EFP usage. It finally leads to the improvement of nutritional state and quality of life in CRC patients.